Pendampingan Pembenahan Instalasi Sistem CCTV untuk Masjid Baitul Rohmah Pudak Payung Semarang - Muhammad Amiruddin; Imadudin Harjanto; Bambang Hadi Kunaryo; Margono Margono (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
Apart from being a place of worship, the mosque has a function to improve community relations in the environment around the mosque in particular. In order to improve community relations, it is necessary to hold several activities involving the community under the auspices of the mosque. In order for community activities to take place, the mosque is equipped with several assets such as electronic devices, sound systems, air conditioning, infaq contacts/charity boxes and some other supporting furniture. So mosque assets need to be maintained in the security aspect. To support the security aspects of the mosque's environment, in this service there will be mentoring and training on the CCTV (Close Circuit Television) system. This service activity is carried out by technicians, mosque congregation and accompanied by a service team, including; needs assessment, field survey, network design and layout, preparation of budget plans and device requirements, device installation and device firmware settings. After being agreed by the team, this service installed 5 camera points to monitor 4 areas, parking area, yard, congregation area and priest area. From the results of this activity, that the installation of cameras at 5 points in accordance with the planned survey results and needs assessment can provide comprehensive monitoring of environmental conditions outside and inside the mosque, so that it can better guarantee security in the mosque and its surroundings.